Synthesis and Antiarrhythmic and Anticonvulsant Activities of Amino Amides and Amino Esters Based on 1-(4-Fluorophenyl)- and 1-[3-(Trifluoromethyl)phenyl]cyclopentane-1-carboxylic Acids - Arustamyan, J. S.; Margaryan, R. E.; Aghekyan, A. A.; Mkrtchyan, G. S.; Muradyan, R. E.; Grigoryan, M. S.; Panosyan, H. A.; Mkryan, G. G. (Russian journal of organic chemistry, 2024)
The alkylation of 2-(4-fluorophenyl)- and 2-[3-(trifluoromethyl)phenyl]acetonitriles with 1,4-dibromobutane gave 1-(substituted phenyl)cyclopentane-1-carbonitriles which were hydrolyzed to the corresponding carboxylic acids by the action of potassium hydroxide in ethylene glycol. The resulting acids were converted to acid chlorides, and the latter reacted with N , N -dialkylaminoalkylamines, as well as with N , N -dialkylaminoalkanols, to produce new amino amide and amino ester derivatives of 1-(4-fluorophenyl)- and 1-[3-(trifluoromethyl)phenyl]cyclopentane-1-carboxylic acids, which were characterized as hydrochlorides. The synthesized compounds were evaluated for their antiarrhythmic and anticonvulsant activities.